Composition and abundance of collembola in primary and logged over forest. - Haneda, Noor Farikhah; Sajap, Ahmad Said; A.B., Idris (2010)

(untitled)
The composition and abundance of collembola among three different forest habitats of the Sungai Lalang Forest Reserve, Selangor Malaysia were compared.The three forest habitats selected were primary forest,5-year old logged over forest(LOF) and 10-year old LOF. Result shows that primary forest had higher total number of Collembola as compared to that of LOF. Members of the entomobryidae had the most number of individual while onychiuidae, and isotomidae was found only in 5-year old LOF. Result of this study implies that primary forest conditions have a significant impact on abundance and composition of collembola communities.